Exploring Drivers of Psychological Traits affecting Investment Intentions of Retail Investors - Oberai, Himani; Saxena, Ankit; Bhardwaj, Shivam; Kaushal, Arun; Dwivedi, Ram Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Investment decisions of an individual are not always based on rational factors. Investor’s decisions on the investment are also impacted by psychological factors. It is often seen that investors take decisions based on some psychological assumptions which are not always logical. This study proposes a conceptual model which is majorly based on Theory of planned behavior (TPB). The proposed model aims at providing insights about how an investor develops his behavioral intention towards investment behavior.Based on theory of planned behaviour, investor’s intention towards investment is determined by a set of constructs viz. positive or favorable attitude of an investor towards investment, subjective norm reflecting the investor’s perception of what their significant or referent group members will think about performing or not performing the behavior, and perceived behavioral control which defines the investor’s control in association to internal and external constraints on taking investment decision.Besides this, the study also highlights that how an investor’s attitude towards the investment behavioral intention is shaped. The conceptual model proposed in the study gives useful insights to the readers as to how an investor’s attitude is built towards investment and then further what are the different psychological dimensions which operate in an investor in order to push him away/towards performing some investment.